1994
DOI: 10.1200/jco.1994.12.10.2043
|View full text |Cite
|
Sign up to set email alerts
|

p53 nuclear overexpression: an independent predictor of survival in lymph node--positive colorectal cancer patients.

Abstract: In node-positive colorectal cancer patients with low preoperative CEA levels, nuclear p53 overexpression as determined by immunohistochemistry on archived tissue is an independent predictor for prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
1
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 32 publications
5
56
1
2
Order By: Relevance
“…Disruption of p53 by gene targeting in human colon cancer cells results in cell resistance to different chemotherapeutic agents, as opposed to wild type cells (35). Hence, loss of p53 in human colorectal cancers may explain the inefficacy of chemotherapy and may be correlated with decreased survival in patients with colorectal adenocarcinomas (36)(37)(38)(39).…”
Section: P53 Tumor Suppressor Genementioning
confidence: 99%
“…Disruption of p53 by gene targeting in human colon cancer cells results in cell resistance to different chemotherapeutic agents, as opposed to wild type cells (35). Hence, loss of p53 in human colorectal cancers may explain the inefficacy of chemotherapy and may be correlated with decreased survival in patients with colorectal adenocarcinomas (36)(37)(38)(39).…”
Section: P53 Tumor Suppressor Genementioning
confidence: 99%
“…Mutations of the TP53 gene have been observed in the progression of colonic polyps to colon cancer (Vogelstein et al, 1988;Fearon and Vogelstein, 1990). We have previously found that p53 nuclear overexpression correlates well with poor survival in colorectal cancer (Zeng et al, 1994). Our hypothesis for the present study is that colorectal tumours with positive or negative p53 nuclear staining may be characterised by aetiological heterogeneity, which could reflect a difference in the causal pathway, or could be indicative of a difference in the magnitude of effect with the same mechanism.…”
mentioning
confidence: 57%
“…We studied a total of 107 (59 males, 48 females) patients with primary colorectal carcinoma. This series was previously studied for the prognostic significance of p53 in colorectal carcinoma (Zeng et al, 1994 PAb 1801 at the concentration of 200 ng 14l-I at 4°C. Sections of a breast carcinoma known to contain mutant p53 protein were used as a positive control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations